Features of changes in sexual function in women in old age - Yu. E. Dobrochotova; A. Z. Khashukoeva; M. I. Agaeva; Z. A. Agaeva (Лечащий Врач, 2021)
The full value of sexual function is a significant aspect of human life. Despite the obvious significance, the sexually-erotic determinants in a person’s life and its important role in the physical, mental and social well-being of women, the discussion of issues related to sexual activity in the representation of the older group remains beyond scientific interest. This article provides an overview of data on the nature and prevalence of sexual dysfunction among older women and discusses modern methods of correcting disorders of sexual function in postmenopausal women.